Wide‐Angle Scattering Halo Analysis and the Evolution of Oriented Amorphous Structure after Elongation Jumps in Some Elastomers. Issue 15 (15th June 2022) - Stribeck, Almut; Schneider, Konrad; Pöselt, Elmar; Eling, Berend; Roth, Stephan V.
Abstract: Amorphous and low‐crystallinity thermoplastic polyurethane elastomers are shot back and forth between two elongation levels ( ε = 0.2 $ε =0.2$ and ε = 1.2 $ε =1.2$ ) and observed between the excitations for 10 s using wide‐angle X‐ray scattering (WAXS) (50 Hz). For orientation analysis, the fiber patterns are projected, expanded in multipoles, and discussed as a function of relaxation time. Normalized WAXS suggests that the oriented halo observed during extension is predominantly due to selective extinction of unfavorably oriented probes (chain bundles). During retraction, neighborhoods and thus clusters are restored. Discussed are the relaxation curves depending on material and the number of load cycles. The separation of the halo into narrow rings introduces "bundle airiness" as a second coordinate. The now bivariate cluster density is the product of two univariate functions. Its factor "airiness distribution" seems to be a material property which is not changed by annealing. In contrast, the bivariate preferred orientation is not product‐separable. Especially with harder materials it shows two bundle ensembles of different airiness. Interactions between the ensembles explain complex trajectories of the orientation–relaxation curves. The formation of the additional airier oriented component is inhibited by annealing in most of the materials studied. In contrast, multiple load changes promote its formation. Abstract : Only bundles of chains probe orientation in the wide‐angle X‐ray scattering of 13 thermoplastic elastomers. Strain destroys neighborhoods and unloading makes neighbors come together again. Hermans' orientation parameter f H $f_{\text{H}}$ and the probe density N $N$ are monitored as a function of both the time elapsed after strain‐jumps and the intra‐probe spacing d a $d_{a}$ . Annealing makes f H ( d a ) $f_{\text{H}}(d_{a})$ unimodal, cycling promotes bimodality.